(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The integration of Information and Communication Technology (ICT) has fundamentally transformed the operational, managerial, and service delivery frameworks of academic libraries, marking a paradigm shift from traditional print-based systems to hybrid and fully digital environments. This study critically examines the extent of ICT implementation and evaluates its effectiveness in enhancing the quality, accessibility, and efficiency of library services among colleges affiliated with Bangalore University and Bengaluru City University. Employing a mixed-method research approach, data were collected from 60 librarians and 240 faculty and student users through structured questionnaires, semi-structured interviews, and observational checklists. The findings reveal that a majority of libraries, particularly those in urban settings, have achieved substantial levels of ICT adoption in areas such as digital cataloguing, online public access catalogues (OPAC), e-resource management, and web-based information services. The integration of automation software, institutional repositories, and subscription-based databases has improved user satisfaction and operational transparency. However, the study also identifies persistent disparities in technological infrastructure, ICT literacy, and staff training across institutions. Many libraries continue to face challenges related to budgetary constraints, inadequate maintenance support, and limited user orientation programs. The study concludes that sustained professional development, adequate financial support, and the establishment of collaborative networks among affiliated institutions are crucial for strengthening ICT-enabled library services. A strategic policy framework promoting technological equity and capacity building is recommended to ensure inclusive and sustainable digital transformation in academic libraries.